Bibliometric dan Systematic Literature Review (SLR): Employee Engagement pada Era Hybrid Working - Eneng Iviq Hairo Rahayu; Zahra Zahra; Fara Mutia; Lilik Yuliawati; Iwan Asmadi (CV Edujavare Publishing, 2026)
This study aims to analyze the development of research on employee engagement in the context of hybrid working through bibliometric analysis and a Systematic Literature Review (SLR) approach. The study employed a mixed-methods design by integrating bibliometric analysis using VOSviewer software and literature synthesis based on the PRISMA protocol. Data were collected from Scopus, Web of Science, and Google Scholar databases covering publications from 2019 to 2024. The literature selection process resulted in 87 articles that met the inclusion criteria. The bibliometric findings indicate that publications related to employee engagement in the era of hybrid working increased significantly after the COVID-19 pandemic, with major themes focusing on psychological aspects, digital technology, leadership, work-life balance, and organizational culture. The SLR results reveal that work flexibility and transformational leadership are the most dominant factors in enhancing employee engagement. In addition, digital technology plays a crucial role in facilitating communication and collaboration among employees. However, hybrid working also presents challenges, including increased work stress and blurred boundaries between personal and professional life. This study contributes theoretically through the development of an integrative model of employee engagement within the hybrid working context and provides practical implications for organizations in designing adaptive and sustainable human resource management strategies in the modern workplace era.